Probiotics, Prebiotics and Synbiotics for Nile tilapia: Growth performance and protection against Aeromonas hydrophila infection - Raissa Bertoncello Cavalcante; Guilherme Silveira Telli; Leonardo Tachibana; Danielle de Carla Dias; Eliana Oshiro; Mariene Miyoko Natori; Wemeson Ferreira da Silva; Maria José Ranzani-Paiva (Aquaculture Reports, 2020)
The use of probiotics, prebiotics and synbiotics provides better growth rates, improves the innate immune system and protection against several bacterial pathogens. The species Aeromonas hydrophila causes high mortality rate and production loss, provoking an antimicrobial overuse. This study aimed to prove the capacity of commercial probiotic DBA® (Bifidobacterium sp, Lactobacillus acidophilus and Enterococcus faecium), prebiotics MOS and chitosan, combined as synbiotics or not to promote Nile tilapia growth performance, innate immune system modulation and protection against A. hydrophila. One experiment with 24 units, duration of 63 days, and another experiment infection assay with A. hydrophila (18 experimental units, individual recirculation system, duration of 15 days) were performed. The treatments were: control, probiotic DBA (PRO), the prebiotics mannan oligosaccharides (Actigen®) (MOS) and chitosan (CHI), and the synbiotics composed of probiotic and MOS (Actigen®) (PRO + MOS), probiotic and chitosan (PRO + CHI). Growth performance, hematology, intestinal histology and immunology, and relative protection level against A. hydrophila were analyzed. Significant differences were observed in the final biomass for the treatments PRO + CHI and CHI when compared with PRO + MOS, and greater individual weight gain in group PRO + CHI in relation to group PRO + MOS. High concentrations of Lactobacillus spp. in intestinal tract of probiotics, prebiotics and symbiotics groups were observed. The treatments PRO + MOS, PRO + CHI and PRO promoted apparent preservation of the intestinal epithelium and stimulated an increase in goblet cells, blood vessels and mast cells, associated to immune system. The symbiotics MOS and DBA® promoted better relative protection level with percentage of 40%. This study recommends the use of probiotics, prebiotics and synbiotics to improve the protection against A. hydrophila infection without growth reduction. Inclusion of feed additives may reduce the application of antimicrobials in fish farming.